PEMILIHAN SUBKONTRAKTOR PT X DENGAN METODE ANALYTICAL HIERARCHY PROCESS - Lilik Zulaihah Rio Patria; Rio Patria (Bina Teknika, 2016)
PT. X is a company engaged in the field of engineering services procurement and construction (EPC), whose scope of work is the provision which has activities such as selecting subcontractors and evaluate the performance of subcontractors and building maintaining relationship with subcontractors. The selection of subcontractors has been less effective, because the show just based on the lowest offer and mere instinct of managers. So that when the project goes arises the problem stems from a subcontractor who is not taken into account before. This research helps decision maker in making the decision to choose a subcontractor in the project Based Oil Flushing (BOF) by integrating Analytical Hierarchy Process (AHP) method. AHP is used to determine the weight of the priority with seven aspect of the three first priorities of quality aspects, financial aspects, and aspects of the company’s reputation, and is also used to determine the weight AHP priorities of the twenty-three criteria with three first priority the offer price, quality assurance, and work experience. Of the four subcontractors research result into the most optimal subcontractor, chosen in accordance with the value of the achievement of targets is limited to the smallest deviation from other subcontractors.